Intelligent M & A : navigating the mergers and acquisitions minefield - Moeller, Scott; Brady, Christopher, 1947- (Chichester, West Sussex : Wiley, 2014)
"Almost 70% of mergers fail, yet deals are essential for growing world-class companies. Therefore they must use all the tools and techniques at their disposal to improve their chances of success. Applying the techniques advocated in this book can help managers beat the odds - and employees themselves - to have an impact on whether a deal will be successful both for the company and for themselves. This book looks at the process of a merger or acquisition and pinpoints the areas where business intelligence can raise the odds of success in each phase of the deal. Using techniques developed by governmental intelligence services and a wide range of recent case studies, quotations and anecdotes, the expert authors from the renowned Cass Business School show how to build success into any M & A situation. The first edition of Intelligent M & A was written in 2006 and published in 2007. This preceded the peak year (2007) of the last merger wave, including the excesses in a number of industries and deals (e.g., financial services with RBS' dramatically failed acquisition of ABN AMRO as a key example), and the global economic downturn that led to a completely new way of operating for many industries and companies. Therefore, there is a need to update the book to incorporate not just more relevant and up-to-date case studies of deals but to show the 'new' way of operating in a post-Lehman environment. Chapters will be comprehensively re-written and populated with new and relevant case studies"--
"This book looks at the process of a merger or acquisition and pinpoints the areas where business intelligence can raise the odds of success in each phase of the deal"--
Introduction to the Second Edition -- The Need for Intelligence in Mergers and Acquisitions -- Business Intelligence -- Designing the Acquisition Process -- Controlling the Advisors -- Identifying the Best Targets -- The Best Defense -- Due Diligence -- Valuation, Pricing, and Financing -- Negotiation and Bidding -- Post-Deal Integration -- Post-Deal Review.
Includes bibliographical references and index.
Machine generated contents note: Introduction to the Second Edition 1 The Need for Intelligence in Mergers and Acquisitions 2 Business Intelligence 3 Designing the Acquisition Process 4 Controlling the Advisors 5 Identifying the Best Targets 6 The Best Defense 7 Due Diligence 8 Valuation, Pricing, and Financing 9 Negotiation and Bidding 10 Post-Deal Integration 11 Post-Deal Review 12 Conclusions Bibliography and References Index.
Print version record and CIP data provided by publisher.
John Wiley and Sons
Keywords: Consolidation and merger of corporations; Business intelligence; Consolidation and merger of corporations -- Management; Organizational change -- Management; Organizational change; Entreprises -- Fusion; Entreprises -- Fusion -- Gestion; Changement organisationnel; BUSINESS & ECONOMICS -- Decision-Making & Problem Solving; Business intelligence; Consolidation and merger of corporations; Consolidation and merger of corporations -- Management; Organizational change -- Management